Mood profile of an America's Cup team: Relationship with muscle damage and jnjuries - Hadala, M.; Cebolla, A.; Banos, R.; Barrios, C. (Medicine & Science in Sports & Exercise, 2010)
Purpose: To describe the mood profile of an America's Cup sailing team during competition and to evaluate the influence of previous injuries occurrence and intensity of physical work on the boat upon mood state. Relationships between mood domains and metabolic markers of muscle damage were also investigated.